TINJAUAN HUKUM TERHADAP PELAKSANAAN ARISAN ONLINE MENURUT HUKUM PERDATA DI INDONESIA - Wulandari, Sri; Hartono; Zulkifli (The Juris, 2024)
Online social gathring is a social gathering activity carried out online or via social media, carried out by several parties using the money transfer method, usually online arisan is carried out using a descending system which is often used on the Instagram platform. The focus of this research is on the analysis of responsibilities and forms of legal protection in online social gatherings. The research used is normative with research methods using a statutory approach and a case approach. The results of this research is:According to law, responsibility is a consequence of the consequences of a person's freedom regarding his actions which are related to ethics or morals in carrying out an action. In online social gatherings, the chairman and members of the social gathering each have responsibilities that must be obeyed and carried out in order to maintain the smoothness and continuity of the online social gathering. It is important before joining an online social gathering, make sure you clearly understand the applicable rules or regulations, be disciplined in paying or handing over money for the social gathering. Legal settlement is a conflict or dispute resolution process that involves the application of legal rules to achieve justice. In the legal context, legal settlement can be carried out through various methods such as mediation, arbitration, litigation and negotiation. Before joining an online social gathering, it would be good to understand what the rules are in online social gathering, such as making a written agreement, dispute resolution mechanisms.